PENERAPAN KURIKULUM JARINGAN SEKOLAH ISLAM TERPADU (JSIT) DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA SMPIT KHOIRU UMMAH REJANG LEBONG - Erwanto Erwanto (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2019)
This research is based on the Application of the Curriculum of the Integrated Islamic School Network (JSIT) in the Formation of Religious Characters of SMPIT Khoiru Students, Ummah Rejang Lebong. SMPIT Khoiru Ummah in implementing its learning applies the Curriculum of the Integrated Islamic School Network (JSIT) curriculum that integrates with the National Local Content curriculum based on Islamic education, which includes the National curriculum (Ministry of Education and Culture), Ministry of Education curriculum and JSIT curriculum. Problem formulation of this study: First, How is the implementation of the Integrated Islamic School Network (JSIT) curriculum in the formation of religious character of SMPIT Chorus Ummah students, Second, how is the content and program of the JSIT curriculum, Third, what are the advantages and disadvantages of the curriculum. In order to find the answer the study used a descriptive qualitative approach and the location of his research at SMPIT Khoiru Ummah with the main data sources obtained through interviews, observation, and documentation. And data analysis techniques are obtained from data reduction, data presentation and data verification by triangulating data. Based on the results of the study, it was found that: 1) The application of the JSIT curriculum could shape the religious character of SMPIT Khoiru Ummah students as evidenced by the internalization of Islamic values on all subjects, local content and program curriculum, 2) JSIT curriculum content and programs shaped, training, workshop, BPI, PRAMUKA SIT, mabit, rihlah, mukhoyam qur’an, putsal, dhuha, English corner, club science, archery, spirituality, tahsin and tahfiz, 3) The advantages of the JSIT curriculum are: students can master general science as well as science Islamic religion, the achievement of special competencies that must be possessed, students are able to do community service in the form of teaching Koran able to memorize 3 juz of the Qur’an and students are more easily directed. In addition, the negative influence of children outside the school is reduced because the child’s time for school is longer. The shortcomings of the JSIT curriculum are seemingly compelling towards students, forcing teachers in the preparation of lesson plans to be in accordance with the peculiarities of JSIT, the learning hours are so crowded.